A data-modelling approach to web application synthesis. (29th October 2004) - Di Ruscio, Davide; Muccini, Henry; Pierantonio, Alfonso
Most web applications are data-intensive, i.e. they rely heavily on dynamic contents usually stored in databases. Website design and maintenance can greatly benefit from conceptual descriptions of both data and hypermedia aspects, i.e. those design dimensions which distinguish this application class: the data upon which the content is based, the way dynamic contents are composed together to form pages, and how pages are linked together in order to move across the application content. The paper proposes Webile, a visual Domain-Specific Language based on UML, which enables a model-driven approach to high-level specification of web applications. In contrast with other approaches, Webile exploits the UML meta-model architecture by serialising the specifications in the XMI interchange format. This representation provides interoperability amongst different operative platforms and enables an XSL transformation-based automatic generation of the applications that are being designed.